Left ventricular diastolic dysfunction in chronic renal failure patients on chronic hemodialysis in Dr. Cipto-Mangunkusumo Hospital : the association with left ventricular mass (Faculty of Medicine Universitas Indonesia, 2006)
Fourty three patients with chronic renal failure undergoing chronic hemodialysis in Division of Nephrology and Hypertension, Faculty of Medicine, University of Indonesia/Cipto-Mangunkusumo Hospital, Jakarta, since October 2003 until February 2004, were examined for echocardiography (2-D, M-mode, Doppler imaging).Diastolic dysfunction was found in 58.1 % of chronic renal failure patients on hemodialysis. There was no significant difference between left ventricular mass in the group with or without left ventricular diastolic dysfunction. (Med J Indones 2006; 15:105-8)